1983
DOI: 10.1007/bf02680352
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of carbonyl compounds in oxidized fats as trichlorophenylhydrazones

Abstract: A rapid determination of the carbonyl compounds in oxidized fats and oils was devised based on formation of trichlorophenylhydrazones (TCPH). Fat in cyclohexane/ether (99:1) was passed through a Florisil column to remove interfering hydrocarbons, and the fat and carbonyl compounds were eluted with ether. The eluate was reacted with trichlorophenylhydrazine with Florisil as a catalyst, and the TCPH were isolated from the fat by chromatography on a Florisil column. The TCPH were separated and quantified by gas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Data from the present study indicated that the differences in oxidative stability as measured by PV and CD were not as distinct in the 60 C accelerated test as in the 28 C test. White and Hammond (28) also found that the differences in measured oxidative stability were smaller in a 60 C storage test than in a room-temperature oxidation test. However, in the current study, there also were not as many differences in the total percentages of unsaturated FA among the oils in test 2 as there were in test 1.…”
Section: Percentages Of Conjugated Dienoic Acid A-d Inmentioning
confidence: 92%
“…Data from the present study indicated that the differences in oxidative stability as measured by PV and CD were not as distinct in the 60 C accelerated test as in the 28 C test. White and Hammond (28) also found that the differences in measured oxidative stability were smaller in a 60 C storage test than in a room-temperature oxidation test. However, in the current study, there also were not as many differences in the total percentages of unsaturated FA among the oils in test 2 as there were in test 1.…”
Section: Percentages Of Conjugated Dienoic Acid A-d Inmentioning
confidence: 92%
“…White and Hammond (12) reported that the reaction of hydroperoxide with the reagent during the formation of the TCPHs resulted in the formation of a small additional amount of carbonyl. To avoid including any carbonyls formed from the hydroperoxides during derivatization in our analytical results, either the hydroperoxides were incubated long enough so that decomposition was complete before the samples were reacted to form derivatives, or the results were corrected.…”
Section: Resultsmentioning
confidence: 99%
“…× 26-cm column filled with 10 g Florisil in pentane/ether (99:1). Hydrocarbons were eluted with 15 mL pentane/ether (99:1), and the carbonyls were eluted with 15 mL ether (4).…”
Section: Methodsmentioning
confidence: 99%